Tailoring Ni based catalysts by indium for the dehydrogenative coupling of ethanol into ethyl acetate - Ming Yin; Jifeng Pang; Jin Guo; Xianquan Li; Yujia Zhao; Pengfei Wu; Mingyuan Zheng (Green Energy & Environment, 2024)
Exploring stable and robust catalysts to replace the current toxic CuCr based catalysts for dehydrogenative coupling of ethanol to ethyl acetate is a challenging but promising task. Herein, novel NiIn based catalysts were developed by tailoring Ni catalysts with Indium (In) for this reaction. Over the optimal Ni0.1Zn0.7Al0.3InOx catalyst, the ethyl acetate selectivity reached 90.1% at 46.2% ethanol conversion under the conditions of 548 K and a weight hourly space velocity of 1.9 h−1 in the 370 h time on stream. Moreover, the ethyl acetate productivity surpassed 1.1 gethylacetategcatalyst−1h−1, one of the best performance in current works. According to catalyst characterizations and conditional experiments, the active sites for dehydrogenative coupling of ethanol to ethyl acetate were proved to be Ni4In alloys. The presence of In tailored the chemical properties of Ni, and subsequently inhibited the C–C cracking and/or condensation reactions during ethanol conversions. Over Ni4In alloy sites, ethanol was dehydrogenated into acetaldehyde, and then transformed into acetyl species with the removal of H atoms. Finally, the coupling between acetyl species and surface-abundant ethoxyde species into ethyl acetate was achieved, affording a high ethyl acetate selectivity and catalyst stability.